A microsatellite study on the genetic distance between suri and huacaya phenotypes in peruvian alpaca (Vicugna pacos) - La Manna, Vincenzo; La Terza, Antonietta; Dharaneedharan, S.; Ghezzi, Silvia; Arumugam Saravanaperumal, S.; Apaza, Nolberto; Huanca Mamani, Teodosio; Bozzi, Riccardo; Renieri, Carlo (CH, 2022)
9 páginas